Association Between Proposed Definitions of Clinical Remission/Response and Well-Being in Patients With Crohn's Disease. (16th September 2021) - Sandborn, William J; Lewis, James D; Panes, Julian; Loftus, Edward V; D'Haens, Geert; Yu, Zhuqing; Huang, Bidan; Lacerda, Ana P; Pangan, Aileen L; Feagan, Brian G
Abstract: Background and Aims: Patient-reported outcomes are recommended endpoints in Crohn's disease [CD] trials. The association between patient-reported general well-being relative to symptoms of diarrhoea and abdominal pain [AP] in patients with moderate to severe CD was explored. Methods: Patients from three randomized, placebo-controlled, double-blind adalimumab or upadacitinib studies with average daily very soft/liquid stool frequency [SF] ≥4 and/or AP score ≥2 at baseline were included. Using electronic diaries, patients reported general well-being [seven-point Likert scale; 1 = worst; 7 = best] in item 10 of the Inflammatory Bowel Disease Questionnaire [IBDQ]. Changes in well-being and clinical outcomes of SF and AP from baseline to week 12 or 16, and the relationship between well-being and clinical outcomes were evaluated using cumulative distribution function and probability density function curves. Results: In total, 858 patients with CD were included [adalimumab, n = 695; upadacitinib, n = 163]. Patients who achieved clinical remission [SF ≤2.8, AP score ≤1.0, neither worse than baseline] were more likely than those not in clinical remission to report IBDQ item 10 response in the 6–7 group category but not IBDQ categories ≤5. Higher IBDQ score for item 10 [6–7] was associated with lower SF and AP score. Greater point increases in IBDQ item 10 were associated with a greater percentage decrease in clinical parameters; a ≥25–30% decrease in SF or AP was associated with a ≥1-point improvement in IBDQ. Conclusions: An association between improvements in patient-reported general well-being and clinical remission/response was observed using outcomes of SF and AP, supporting the clinical remission/response endpoint definitions used in clinical studies of CD. Clinical Trial Registrations [ClinicalTrials.gov]: NCT00077779 [CHARM]; NCT00348283 [EXTEND]; NCT02365649 [CELEST].